Tổng quan nghiên cứu phát triển đội ngũ giảng viên đại học khối ngành kĩ thuật - công nghệ theo tiếp cận CDIO - Phạm Phương Tâm, Phạm Phương Tâm; Lê Thị Thanh Thuỷ, Lê Thị Thanh Thuỷ; Nguyễn Thị Ngọc Trinh, Nguyễn Thị Ngọc Trinh (Tạp chí Giáo dục, 2026)
The development of university teaching staff in engineering and technology through the CDIO approach is increasingly essential. This direction significantly improves the effectiveness of high-quality workforce training, aligning with the growing demands of both domestic and international labor markets. This paper presents an overview of published research on faculty development and CDIO-based approaches by synthesizing literature from reputable domestic and international sources. In addition to providing a valuable reference on the development of teaching staff in engineering and technology, this paper also serves as a foundation for further exploration and application of the CDIO approach - an advanced educational model that aligns with UNESCO’s four pillars of education for the 21st century.